The Effect of Empathy Levels of Female School of Physical Education and Sports Students on Problem Solving Skill Levels - Akpinar, Öznur (Asian Journal of Education and Training, 2020)
This research is made in order to find whether the empathy levels of female school of physical education and sports students’ effect on problem solving skills by detecting their empathy and problem solving skills and by exhibiting whether the empathy and problem solving skills differ from according to demographic characteristics. In the research, The Empathic Tendency Scale developed by Dökmen (1988) and The Problem Solving Inventory developed by Heppner and Peterson (1982) adapted into Turkish by Sahin, Sahin, and Heppner (1993) is used on the 167 female students studying at Karamanoğlu Mehmetbey University school of Physical Education and Sports in the 2019-2020 academic year. The correlation analysis is done with t and one way Anova tests in the evaluation of the gathered data’s because of the gathered data’s show parametric distribution. As a result of the research, the empathy levels of the students who attended the research is x= 68,8323 and problem solving skills are detected as x=92,2814. Also it is detected that, the female students included in the research have empathy and problem solving skills over intermediate level and empathy levels effect problem solving skills.